THE INFLUENCE OF FINANCIAL LITERACY, QUALITY OF FINANCIAL LEARNING AND FINANCIAL PLANNING ON STUDENTS' PERSONAL FINANCIAL MANAGEMENT - Ni Putu Lidia Marini; Luh Gede Putri Kusuma Pekerti; I Gusti Agung Sasih Gayatri (Universitas Mahendradatta Denpasar, 2024)
This research is based on a formulation of problems, namely whether there is an influence of financial literacy on student personal financial management, whether there is an influence on the quality of financial learning on student personal financial management, whether there is an influence of financial planning on student personal financial management. The benefit of this research is that it can contribute and support the progress of financial literacy, know the factors that affect financial management, and can add insight in the field of financial management. This type of research is a type of quantitative descriptive research with data collection techniques through interviews, observation, documentation and questionnaire distribution to active students at universities, Faculty of Business and Tourism, Triatma Mulya University, PSDKU Jembarana using Likert scale. The population in this study was 100 students of the Faculty of Business and Tourism, Traitama Mulya University, PSDKU Jembrana. The sampling technique in this study used purposive sampling techniques, with 90 samples. The data analysis technique used is a multiple linear regression analysis technique. The results of this study stated that financial literacy has a positive effect on student financial management, the quality of financial learning has a positive effect on student financial management, and financial planning has a positive effect on student financial management.